Are the Contentious Issues of Exchange Rate Misalignment in Nigeria a Prelude to the Country’s Currency Crisis? - Rafindadi, Abdulkadir Abdulrashid (International Journal of Economics and Financial Issues, 2015)
Several pioneering studies have established that the period of exchange rate misalignment is characterized by currency appreciation and depreciation. These studies conclusively assert that if currency overvaluation occurs beyond a minimum threshold it can render an economic system vulnerable to currency crisis, in view of this, is the Nigerian economy in a state of currency crisis? What impact does the period of currency crisis have on the Nigerian economy and what factors are responsible in aggravating the position of the crisis within the context of the Nigerian economy? To ensure this, we applied the permanent equilibrium exchange rate (PEER) and the behavioral equilibrium exchange rate (BEER) in estimating the misalignment in Nigeria. While the Logit and Probit models were used to determine the impacts of the crisis on the Nigerian economy. The study used quarterly data from 1980Q1 to 2011Q4. The findings of the study established the existences of high degree of currency overvaluation reaching an unprecedented level above 46% in the last quarter of 2011. A similar worsening trend was observed in the case of undervaluation. The results of the Logit and Probit models, on the other hand, reveal that the Nigerian economy is in a state of currency crisis. The study discovered how external debt, money growth rate and domestic credit growth rate to be the more likely compounding factors to the crisis in Nigeria. Although the study discovered that the momentum of the crisis has no effect on the county’s GDP growth rate. Nevertheless, these problems were discovered to be the aggravating agents of the crisis in Nigeria. We recommend the establishment of frameworks that are consistent with boosting productivity and the application of synergistic monetary policy models that will not only ensure a sustainable and improved value of the local currency, but that which could create its foreign demand, among other things. Keywords: BEER; PEER; exchange rate misalignment; currency crisis. JEL Classifications: F3; F4; F31; F40